2009
DOI: 10.1007/s10964-009-9494-9
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Emotional Distress: The Role of Family Obligations and School Connectedness

Abstract: The current study draws upon ecodevelopmental theory to identify protective and risk factors that may influence emotional distress during adolescence. Hierarchical regression analyses were used to examine the relationship among family obligations, school connectedness and emotional distress of 4,198 (51% female) middle and high school students who were primarily (59%) European American. The overall model explained 21.1% of the variance in student emotional distress. A significant interaction effect was found i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 40 publications
5
21
0
Order By: Relevance
“…Although the main data were gathered from adolescents and parents, the use of independent reports of family functioning, school bonding, academic competence, peer relationships, and antisocial or delinquent behaviors complemented these sources, and enhanced the reliability and generalizability of our findings. The pattern of results obtained in our study is consistent with the theory26,37,59,102 and past research using well-validated measures,72,79 and thus provides fair tests of our study’s hypotheses.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although the main data were gathered from adolescents and parents, the use of independent reports of family functioning, school bonding, academic competence, peer relationships, and antisocial or delinquent behaviors complemented these sources, and enhanced the reliability and generalizability of our findings. The pattern of results obtained in our study is consistent with the theory26,37,59,102 and past research using well-validated measures,72,79 and thus provides fair tests of our study’s hypotheses.…”
Section: Discussionsupporting
confidence: 91%
“…The results from our study may have important implications for designing and implementing preventive interventions to prevent or reduce HIV-risk behavior and other health outcomes among AA adolescents. It is important to intervene in adolescents’ ecodevelopmental contexts to prevent problematic adolescent outcomes, because both self and context may provide maximal protection against risks of problem behaviors, depression, and their sequelae (eg, substance use, suicidal ideation) 3,27,94,102106. While adolescence is a time of growing independence, our study findings suggest that parents should continue to be involved in their adolescents’ lives and monitor and guide them through the challenges of this period.…”
Section: Conclusion and Practical Implicationsmentioning
confidence: 99%
“…[1][2][3][4][5][6] Studies from the educational literature have suggested features of middle and high school environments that may have an impact on emotional well-being, such as school size and ratio of students to teachers, pedagogic practice, and quality of interactions within the school. [7][8][9][10] Observational studies have found evidence that positive peer and teacher relationships, [11][12][13][14][15] a school climate judged favorably on aspects such as safety and fairness, 14,16,17 and feelings of school "connectedness" or "bonding" [18][19][20][21] are all associated with better emotional health.…”
mentioning
confidence: 99%
“…This change might begin at the transition from primary school to secondary school because of greater bullying, greater aggression, fewer peer affiliations, or less perceived school support (Niehaus et al, 2012;Pellegrini & Long, 2002). Moreover, the fall in SOSB might continue during secondary school (Cupito et al, 2015;Wilkinson-Lee et al, 2011). Hence, researchers can test whether providing more support to secondary school students or more activities to engage them can improve their SOSB.…”
Section: Discussionmentioning
confidence: 99%
“…Although generally stable in primary school, students' SOSB can plummet during their transition to secondary school, due to greater bullying/aggression, weaker peer affiliations, or weaker perceived school support (Niehaus, Rudasill, & Rakes, 2012;Pellegrini & Long, 2002). Some empirical studies have shown that students' SOSB starts dropping at Grade 6 (Furrer & Skinner, 2003;Tian et al, 2016) and keeps dropping during secondary school (Cupito, Stein, & Gonzalez, 2015;Wilkinson-Lee, Zhang, Nuno, & Wilhelm, 2011). In contrast, another study found that students' SOSB remained stable during secondary school (Hughes, Im, & Allee, 2015).…”
Section: Sosb From Primary School To Secondary Schoolmentioning
confidence: 99%